The association between osteoporosis prevention and the reduction of falls in the elderly: A literature review (Research, Society and Development, 2025)
Population aging is a global phenomenon, increasing in recent years, with significant advances in healthcare, improved living conditions, and the impact of disease. However, this increase in life expectancy leads to a higher prevalence of age-related chronic diseases, including osteoporosis, which stands out for its clinical importance in the quality of life of older adults. It is characterized by a decrease in bone mineral density and an increased risk of fractures, especially among the elderly. Falls are one of the most significant causes of morbidity and mortality, influenced by several factors such as comorbidities, muscle fragility, and others. This narrative review aimed to evaluate the relationship between osteoporosis prevention and a decrease in falls among older adults. Studies published between 2020 and 2025 in the SciELO, PubMed, LILACS, and Cochrane Library databases were used. The results indicate that adjusted calcium and vitamin D supplementation, multifactorial interventions, and physical exercise programs help reduce the incidence of falls. The literature suggests that integrated strategies offer greater benefits than isolated approaches. It concludes that public policies and community actions aimed at preventing osteoporosis reduce falls among older adults and their social and economic impacts.